Le profil motivationnel d'étudiants en formation initiale à l'enseignement au Québec au regard du développement de la compétence à communiquer oralement : premiers résultats d'une étude longitudinale - Priscilla Boyer; Geneviève Messier; Christian Dumais; Sylvie Viola
The ability to communicate orally is an essential transversal skill for teaching. Teachers continually call on it during their interactions with students, colleagues, and parents. Development of this skill is one of the early objectives of teacher training, and programs offered in the two Quebec universities participating in this study are no exception, although each institution has chosen different educational strategies. At both the Université du Québec à Trois-Rivières (UQTR) and Université du Québec à Montréal (UQAM), oral communications skills are assessed in several courses and internships, but at UQTR they are also taught in specific courses of certain programs. At UQAM these skills are not taught, but are evaluated by means of an oral presentation whose failure requires students to take upgrading courses. It is reasonable to assume that these educational strategies influence differently students' motivational profiles relative to these skills, particularly with regard to feelings of self-efficacy, but the extent of this influence is unknown. Given the significance of motivation on student persistence in higher education (Dupont, De Clercq et Galand, 2015), we have begun a four-year, mixed-type longitudinal study to describe these changes. The main objective of this article, written in the first year of the study, is to describe the motivational profile of students beginning their undergraduate studies at the two participating universities.